(untitled) (Studia austriaca, 2019)
This article focuses on the comics of the Austrian artist Nicolas Mahler. Selected comics from Franz Kafkas nonstop Lachmaschine (2014) will be analysed as ‘minimalistic form’ and inter-spatial phenomena. In Mahler’s so-called ‘graphic anecdotes’, inter- and transmediality become evident in a variety of ways: in the form and organization of anthology, the construction of pseudo-epigraphs, and the accentuation of ‘transition’ and ‘in-between’. As they address and reflect on the position of comics in the literary field, they also contribute to the current discussion about graphic narrative